A Comparative Study Of Young- Aged Adults And Middle-Aged Adults Consumers Usage Of Digital Marketing Platforms In The Selection Of Food And Beverage Outlets ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: The promotion of brands via the internet and other digital communication channels is known as digital  marketing, sometimes known as online marketing. Digital marketing is quite important for the restaurant industry as well.  Objective: The current study focuses on several online channels, like as websites, social media, email marketing, telephone  marketing, etc., and how young- aged adults and middle-aged adults consumers, use these platforms to choose F&B  establishments in Lucknow City. Methodology: Central tendency technique was implemented to achieve the objectives where  weighted mean score was calculated for all the parameters and based on the weighted mean score, ranking of various  parameters has been given. Results:The findings of the first objective revealed that most influential digital marketing strategy  which influence young adults consumers selection of F&B outlet are marketing through food delivery portals like Swiggy,  Zomato etc.(Rank 1 with Weighted Mean Score of 4.13) followed by paid social media marketing (marketing on YouTube)  (Rank 2 with Weighted Mean Score of 4.12) and marketing through social media platforms like Facebook, Twitter and  Instagram (Rank 3 with Weighted Mean Score of 4.06). The findings of the second objective revealed that most influential digital  marketing strategy which influence middle-aged adults consumers selection of F&B outlet are marketing through websites  (Rank 1 with Weighted Mean Score of 4.17) followed by online reviews about the outlets (Rank 2 with Weighted Mean Score of  4.13) and marketing through social media platforms like Facebook, Twitter and Instagram (Rank 3 with Weighted Mean Score  of 4.05). Conclusion: Swiggy, Zomato etc. followed by paid social media marketing (marketing on YouTube) and marketing  through social media platforms like Facebook, Twitter and Instagramwere preferred by young aged andwebsite and online  review for middle aged consumers.
Keywords: Young Adults; Middle- aged Adults; F&B Outlets; Lucknow City